The penalty of confiscation in Iraqi legislation - Aziz, Sardar Ali (Journal of Legal and Political Studies, 2015)
The Confiscation in the Iraqi Punishment law number (111) for the year 1969 modified, is a compulsory and complementary punishment imposed on the person who is convicted with adjudication after being judged with an original punishment on a felony or delinquency, which is focusing on the tools used to commit the crime or to be used in or taken from. However , the Iraqi legislator cited some specific Iraqi punishment laws ( the law of foreigner residency number (118) for the year 1978 and the Law of passports number (32) for the year 1999 and the Law of battling terrorism for the Kurdistan Region number (3) for the year 2006) the confiscation as a an optional punishment. and in these Laws, all the Sentenced capital will be confiscated with no condition of using, preparing taken for committing the crime. and this type of confiscated is contradicting with the principle of personalizing the punishment, and leads to a direct harm on none sentenced ones. and conflicts with the target of the guests implementation program to help them to save some of their working wages to relay on facing the life difficulties after leaving the enterprise reform, and this is why such confiscation cannot contribute in eliminating crimes.
Keywords: compulsory ,complementary; punishment; ,convicted